2016
DOI: 10.1155/2016/6484713
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Human iPSCs in Neurological Diseases: From Bench to Bedside

Abstract: In principle, induced pluripotent stem cells (iPSCs) are generated from somatic cells by reprogramming and gaining the capacity to self-renew indefinitely as well as the ability to differentiate into cells of different lineages. Human iPSCs have absolute advantages over human embryonic stem cells (ESCs) and animal models in disease modeling, drug screening, and cell replacement therapy. Since Takahashi and Yamanaka first described in 2007 that iPSCs can be generated from human adult somatic cells by retroviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Since they possess great potential for personalized regenerative medicine, they are investigated as a possible therapeutically competent cell population by our [37] and other groups [reviewed in 43]. Neural progenitors (hiPS-NSC) used in this study were derived from human iPSC and seeded on Col-CS and Col-DAC scaffolds for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Since they possess great potential for personalized regenerative medicine, they are investigated as a possible therapeutically competent cell population by our [37] and other groups [reviewed in 43]. Neural progenitors (hiPS-NSC) used in this study were derived from human iPSC and seeded on Col-CS and Col-DAC scaffolds for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evidence that transplantation of mesenchymal stem cells may lead to tumours, there is riskiness, wherefore this aspect should be inspected before PDLSCs transplantation. Furthermore, the study provided by Xie and Tang [32] concluded that undifferentiated PDLSCs triggered several immune responses with high lymphocytic infiltration and elevated IFN-γ secretion, they suggested that in vitro differentiation may alter stem cell immune properties. Regardless of the fact that PDLSCs suppressed the immune response before and after osteogenic induction before transplantation the immune properties of PDLSCs should be investigated [33].…”
Section: Provenance Of Dental Stem Cellsmentioning
confidence: 99%
“…In addition, epigenome editing has the potential to facilitate stem cell therapy. In recent years, iPSCs have been a major source for cell replacement therapy due to its accessibility and pluripotency [ 78 82 ]. iPSCs experience active and delicate epigenome reset to become differentiated cells, and vice versa [ 83 ].…”
Section: Introductionmentioning
confidence: 99%